Sistema de gestión de mantenimiento para la planta de trituración de material pétreo en el Gobierno Autónomo Descentralizado provincial de Santo Domingo de los Tsáchilas, año 2014 - Mullo Chango, Julio César (2015)
The stone crushing plant material Autonomous Decentralized Provincial Government of Santo Domingo de Los Tsáchilas has a significant amount of equipment and machines for the production of aggregates of stone material within the industrial plant, the same as in not having a system of maintenance management, contingencies occur frequently delaying production, generating economic losses affecting the planning and budget of this public institution. In order to meet the objectives in research, deductive, analytical and synthetic methods were used; the types of field research and descriptive literature, were held in the place where the research was conducted; research techniques where a survey of the population under study was conducted in a total of 6 people working in the crushing plant, resulting in a 100% acceptance on the implementation of a maintenance management system were used. The calculation of the current efficiency of the plant resulted in a value of 36.54%, which is considered very low; where Pareto analysis showed that 57.93% of all problems are caused by damage to the machine due to lack of maintenance and that the annual cost of downtime amounted to a value of $ 232,052.70. The actions for continuous improvement were established using maintenanc management indicators, including indicators of effectiveness, performance indicators and efficiency indicators. Besides the established maintenance schedule organized systematically and clearly shows a good organization for frequent stops at each of the teams crushing plant inspections.